2018
DOI: 10.1371/journal.pgen.1007488
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic expression patterns of Irx3 and Irx5 during germline nest breakdown and primordial follicle formation promote follicle survival in mouse ovaries

Abstract: Women and other mammalian females are born with a finite supply of oocytes that determine their reproductive lifespan. During fetal development, individual oocytes are enclosed by a protective layer of granulosa cells to form primordial follicles that will grow, mature, and eventually release the oocyte for potential fertilization. Despite the knowledge that follicles are dysfunctional and will die without granulosa cell-oocyte interactions, the mechanisms by which these cells establish communication is unknow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 65 publications
1
36
2
Order By: Relevance
“…Later in ovarian development, upon germline nest breakdown, Irx3 expression expands to include both somatic cells and oocytes (Fu et al, 2018). β-Catenin is also present in oocytes at this stage as shown by our immunohistochemistry results from ovaries at E14.5 and P7 and supported by previous reports (Figs S1 and S2) (Yan et al, 2019;Bothun and Woods, 2019;Kumar et al, 2016;Usongo et al, 2012;Chassot et al, 2011;Jameson et al, 2012).…”
Section: β-Catenin Activity Correlates With Irx3 and Irx5 Expressionsupporting
confidence: 92%
See 4 more Smart Citations
“…Later in ovarian development, upon germline nest breakdown, Irx3 expression expands to include both somatic cells and oocytes (Fu et al, 2018). β-Catenin is also present in oocytes at this stage as shown by our immunohistochemistry results from ovaries at E14.5 and P7 and supported by previous reports (Figs S1 and S2) (Yan et al, 2019;Bothun and Woods, 2019;Kumar et al, 2016;Usongo et al, 2012;Chassot et al, 2011;Jameson et al, 2012).…”
Section: β-Catenin Activity Correlates With Irx3 and Irx5 Expressionsupporting
confidence: 92%
“…Here, we used in vitro, ex vivo and in vivo approaches to provide a direct link between canonical Wnt/βcatenin signaling and Irx3 and Irx5 expression within the somatic cell population of the developing ovary. In addition, we previously showed that both Iroquois factors emerge in germ cells in late stages of ovarian development (Fu et al, 2018), but here we report that their regulation in this cell type is independent of β-catenin. Based on these data, we developed a model to describe regulation of Irx3 and Irx5 expression within the somatic cell population (Fig.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations